Positive education of stoic warriors as reflective practitioners in the profession of arms. Issue 1 (2nd January 2017) - Stricker, Andrew G.; Arenas, Fil J.; Westhauser, Todd C.; Hawkins-Scribner, Toni
Abstract: This paper traces connections between Stoicism and Positive Psychology for helping to inform and guide the education of warriors in the Profession of Arms. Peterson and Seligman advocate six core virtues and associated character strengths, which the authors illustrate from the practice of leadership education at the Squadron Officer School and The Air University. A synopsis of Costa and Kallick's Habits of Mind is introduced to illustrate how awareness of the ways virtue and character strengths can guide the reflective warrior with wisdom and determined action. The authors also highlight insights from the work of Chris Argyris and Donald Schön on double-loop learning, reflective-thinking-in-action, and couple those insights with Dietrich Dörners' emphasis on the advantages of simulations to offer experimentation by practitioners to better prepare them 'think of, and then do, the right things at the right times and in the right way.' Finally, a virtual world learning simulation developed by the authors to support student experimentation with double-loop learning on character strengths and habits of mind is described to illustrate the art-of-the-possible for the positive education of stoic warriors.